Spontaneous Resolution of Nontraumatic Acute Spinal Subdural Hematoma - Yang, Na-rae (The Korean Neurosurgical Society, 2011)
Spinal subdural hematoma (SSDH) is an extremely uncommon condition. Causative factors include trauma, anticoagulant drug administration, hemostatic disorders, and vascular disorders such as arteriovenous malformations and lumbar punctures. Of SSDH cases, those that do not have any traumatic event can be considered cases of nontraumatic acute spinal subdural hematoma, which is known to have diverse clinical progress. Treatment typically consists of surgical decompression and cases in which the condition is relieved with conservative treatment are rarely reported. We report two nontraumatic acute spinal subdural hematoma patients who were successfully treated without surgery.